‘‘Naked’’ gold nanoparticles supported on HOPG: melanin functionalization and catalytic activity - González Orive, A. (2011)
Reductive electrodesorption has been used to produce ‘‘naked’’ gold nanoparticles (AuNPs) 3 nm in size on HOPG from different thiolate-capped AuNPs. The clean AuNPs transform the electrocatalytic inert HOPG into an active surface for hydrogen peroxide electroreduction, causing a lowering of the cathodic overpotential of 0.25 V with respect to the Au(111) surface. Compared to the plain gold substrates, the nanostructures promote only a slight increase in the hydrogen evolution reaction. In a second modification step a 1 nm thick melanin–iron coating is electrochemically formed around the AuNPs. This ultrathin melanin–iron coating largely improves the catalytic activity of the bare AuNPs for both hydrogen peroxide electroreduction and hydrogen evolution reaction. This strategy, which integrates electrochemistry and nanotechnology, can be applied to the preparation of efficient ‘‘naked’’ AuNPs and organic-iron capped AuNPs catalysts.